The impact of the COVID public policies on the Chilean households. Issue 18 (24th October 2021) - Madeira, Carlos
ABSTRACT: This work uses survey data to study the immediate impact of the public policies implemented during the COVID crisis on the Chilean households. I show debt deferral initiatives only reach a few highly indebted agents, especially concentrated on richer families. Tax relief measures had a broad reach across the population, but with little financial impact. However, income and expenses support had both a wide reach and a strong impact on households, especially for poorer families. A broadening and scaling up of policy efforts should, therefore, focus on direct income support for families.